Two new species of Quichuana Knab (Diptera: Syrphidae) from the paramo ecosystems in Colombia - Montoya, Augusto L.; Ricarte, Antonio; Wolff, Marta (Zootaxa, 2017)
Two new species of Quichuana Knab (Diptera: Syrphidae), Quichuana citara Montoya & Wolff sp. n. and Quichuana nigropilosa Montoya & Ricarte sp. n. are described from highlands of the Colombian Andes. Images of type material, including drawings of male genitalia are provided. An adjustment for the latest identification key for the Quichuana species and distribution maps for those species occurring in Colombia are given.